The insertion of the «decision-surprise prohibition» in the due process of law in the Brazilian experience and the new Code of Civil Procedure of 2015: reflections destined to the Peruvian law - Zufelato, Camilo (2017)
This article analyzes the so-called surprise-decision prohibition as a rule that follows from the due process of law and as an innovation of the Brazilian New Code of Civil Procedure 2015, observing its incidence. It concludes that this prohibition is part of the right of defense and therefore applicable without express legal prevision, as is the case of Peruvian law.